Menakar Kinerja Keuangan dengan Menggunakan Rasio Solvabilitas - Bella Puspita Rininda; Yuli Fitriani; Azizah Azizah (Jurnal Manajemen dan Bisnis, 2021)
This study aims to measure the financial performance of PT AKR Corporindo Tbk’s 2015-2019 financial statements using the solvency ratio. The method in this research is quantitative. The subjects in this study were the financial statements of PT AKR Corporindo Tbk for the years 2015-2019 using the solvency ratio. The results of this study indicate that the assessment of financial performance at PT AKR Corporindo Tbk, for debt to asset ratio is considered not good because it exceeds the industry average standard set, for debt to equity ratio is considered healthy even though it exceeds the industry average standard, because large funds are obtained from short-term debt, namely debt business, and the long term debt to equity ratio is also considered good because it is below the industry average standard. The results of this study indicate that the solvency ratio at PT AKR Corporindo Tbk has decreased and increased based on industry standards.